2006
DOI: 10.1016/j.pain.2006.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment, anxiety, and pain self-efficacy as predictors of pain intensity and disability

Abstract: Pain self-efficacy and anxiety have each been shown to contribute substantially to pain intensity and pain-related disability. Although adult attachment theory has been related separately to chronic pain, anxiety, and self-efficacy, it has not before been investigated with either pain self-efficacy or anxiety in the context of chronic pain. This study investigated the interrelations between these aspects of the chronic pain experience and their relative contributions towards pain intensity and disability. A cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
141
5
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(166 citation statements)
references
References 36 publications
15
141
5
5
Order By: Relevance
“…Similarly, in a sample that included both pain patients and community volunteers, anxious attachment was associated with higher levels of pain intensity and pain-related suffering (MacDonald & Kingsbury, 2006). Among chronic pain patients being treated at a multidisciplinary pain clinic, those who scored high on attachment avoidance and low on pain self-efficacy had particularly high levels of pain intensity (Meredith et al, 2006a). However, other studies have failed to find significant associations between attachment and pain intensity: Williamson et al (2002) measured attachment in children having persistent disease-related pain and their caregivers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, in a sample that included both pain patients and community volunteers, anxious attachment was associated with higher levels of pain intensity and pain-related suffering (MacDonald & Kingsbury, 2006). Among chronic pain patients being treated at a multidisciplinary pain clinic, those who scored high on attachment avoidance and low on pain self-efficacy had particularly high levels of pain intensity (Meredith et al, 2006a). However, other studies have failed to find significant associations between attachment and pain intensity: Williamson et al (2002) measured attachment in children having persistent disease-related pain and their caregivers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pain severity might correlate to anxiety and fears [8,12], poor pain coping [28], anger in men [21], and pain duration [28].…”
Section: Fear Anger and Durationmentioning
confidence: 99%
“…These results correspond to the central purpose of this study and are consistent with our initial predictions, suggesting that individual differences in the perception and expression of pain reflect a person's attachment needs, ability to regulate negative emotions 17 and different abilities to cope with pain. 24 Together, these results seem to depict attachment insecurity as a potential risk factor which can lead to poor coping with pain and maladjustment; and attachment security as a more adaptive trait and an important inner resource in the face of stress-inducing events, allowing the individual to positively appraise stressful events and turn to others for support and comfort. Although unexpected, the lack of a significant association between attachment style and post-delivery pain may result from differences in the experience of this important period (the first mother-baby contact), as it is possible that the pain experienced may be influenced by positive emotions that usually characterize the early postpartum period.…”
Section: Discussionmentioning
confidence: 91%
“…21,22 Other studies, however, have reported no association between attachment and pain intensity. 13,[23][24][25] Given these conflicting findings, and given that, to the best of our knowledge, no studies have investigated how attachment is associated with labour pain, this study aimed at assessing the relevance of attachment styles to the prediction of pain during labour and post-delivery.…”
mentioning
confidence: 99%